Hak Restitusi Bagi Anak Korban Tindak Pidana Kekerasan Seksual - Silma Nurhaurima; Zulkarnaen Koto; Dyah Sulastri Dewi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2021)
The State may not discriminate between one person and another in the fulfillment of human rights because everyone is essentially the same subject in the eyes of the law. This is in accordance with Article 28d, paragraph 1 of the Republic of Indonesian Constitution of 1945. In principle, fair and equal treatment before the law applies not only to adults or people of sufficient age, but also to ensure the fulfillment of children's rights. One form of legal protection for victims of sexual violence is to get restitution. This study uses the approach and concept of the rule of law that applies in the legal system in Indonesia regarding restitution for Child Victims of sexual violence, namely PP Number 43 of 2017 juxtaposed with various cases of fulfilling the right of restitution for Child Victims of sexual violence at UPT P2TP2A DKI Jakarta. In an effort to fulfill the right of restitution for Child Victims of the crime of sexual violence, it is necessary to implement a legal rule that regulates this matter, both in resolving problems if there is a conflict in the fulfillment of the right to restitution.